Salt Composition of Clay Soils and Its Variation with Long-term Water Filtration in Republic of Kalmykia - DORDZHIEV, Anatoly A.; DORDZHIEV, Anatoly G.; SANGADZHIEV, Mergen M.; RUBEKO, Leonid M.; ONKAEV, Victor A. (Journal of Environmental Management and Tourism; Vol 9 No 1 (2018): JEMT Volume IX Issue 1(25) Spring 2018, 2018)
Knowledge of soils types in a certain area allows to predict the stability of the system. Therefore, the purpose of the work is to determine the salt composition of clayey soils and its variation with long-term water filtration, for example, the Republic of Kalmykia. For a detailed study of the topic, the authors carried out various experiments that were based on physico-chemical analyzes of samples and monoliths selected from different regions of Kalmykia. For this, water-soluble salts found in clay soils were considered. Basically, these are three groups: readily soluble, mildly soluble and hardly soluble. Chemical analyzes of chloride, sulphate and carbonate salts of sodium, potassium, magnesium and calcium were conducted on the basis of the Kalmyk State University. Separately attention was paid to the ion-exchange process and, in particular, to the transition from the solid phase to the pore solution. In connection with the strong mineralization of groundwater in the republic, the monoliths are mineralized to 10-20 g / l and in terms of chemical composition, chloride-sodium and sulfate-chloride. Calcium carbonates and gypsum are considered separately depending on the depth of the monolith. On the basis of the experiments carried out, plots of the dependence were plotted in different mineral constituents. It has been established that in gypsum and gypsum-bearing rocks the correlation coefficients for loam and sandy loam are low. The desalinization factor is more than 50%, and the desalinization is uneven in all monoliths taken from different depths. In sandy loam these parameters are lower by 20%. Separately, the parameters of exchange of mineral, disperse composition and the presence of organic substances are considered. The results will allow engineers, designers, practitioners and students to use the results in their daily work.